A review of antenatally-diagnosed congenital heart disease in a Western Cape tertiary facility: outcomes and diagnostic discrepancy - Smith, Damian (Department of Paediatrics and Child Health, 2025)
Objective: To describe the cases of fetal congenital heart disease (CHD), the diagnostic discrepancy (DD) between pre- and postnatal echocardiography (echo) and their outcomes in a state tertiary facility in the Western Cape. Study design: A retrospective descriptive study was conducted on 106 cases of structural CHD diagnosed at the Groote Schuur Hospital (GSH) Maternal Fetal Medicine Unit (MFMU) between January 2018 and December 2019. Primary measurements included maternal obstetric data, fetal diagnosis, extracardiac and genetic abnormalities, pregnancy outcome, postnatal Echo results, intervention and outcomes (catheterisation, surgery). Results: At first presentation to the MFMU, median maternal age was 32 years (Interquartile range (IQR: 26 – 38 years), with a median gestation of 21 completed weeks (IQR: 19 – 25 weeks) and a mean BMI of 28.1 (± 6.8). Amniocentesis was performed in 43/106 cases (40.6%), with a positive genetic abnormality in 23/43(53.5%), highest in the IUFD group (75.0%). Of the cases diagnosed, 21/106 were terminated (n=19.6%), intrauterine fetal death (IUFD) occurred in 21/106 cases (n=19.6%) with 62 live births (n=58.5%). In 2/106 cases there was no record of delivery (n=1.9%). DD rate was 16/47 (n=34.0%). Atrioventricular septal defect was both the commonest prenatal CHD diagnosis and most associated with DD. Conclusions: The DD rate of AVSD seen in the study carries important management implications both during pregnancy and in the immediate post-natal period, highlighting the critical importance of accurate fetal diagnosis. Increasing prenatal screening capacity, regular audit, and prenatal collaboration with paediatric cardiology may improve diagnostic accuracy.